1996
DOI: 10.1007/bf00196786
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition and environmental factors leading to the development of insulin-dependent diabetes mellitus in Chilean children

Abstract: This study was designed to examine the hypothesis that some environmental factors increase the risk for insulin-dependent diabetes mellitus. Data on dietary history was collected from 80 diabetic children from the Santiago de Chile Registry and from 85 nondiabetic control subjects who were comparable in terms of age, sex, and ethnic characteristics. Early exposure was defined as the ingestion of food sources other than maternal milk before 3 months of age. To define genetic susceptibility to insulin-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 30 publications
3
43
0
3
Order By: Relevance
“…Also, the different susceptible or protective HLA risk alleles, or both, could affect the influence of specific environmental factors in initiating and promoting the autoimmune process. It has been implied that an even stronger association between breastfeeding and diabetes might have been detected in previous case-control studies, if the cases and control subjects had been genetically matched [8] and this hypothesis has actually been confirmed by a Chilean study [22]. Those children who tested positive for all four diabetes-associated autoantibodies most probably have an ongoing beta-cell destructing process in their pancreatic islets.…”
Section: Discussionmentioning
confidence: 88%
“…Also, the different susceptible or protective HLA risk alleles, or both, could affect the influence of specific environmental factors in initiating and promoting the autoimmune process. It has been implied that an even stronger association between breastfeeding and diabetes might have been detected in previous case-control studies, if the cases and control subjects had been genetically matched [8] and this hypothesis has actually been confirmed by a Chilean study [22]. Those children who tested positive for all four diabetes-associated autoantibodies most probably have an ongoing beta-cell destructing process in their pancreatic islets.…”
Section: Discussionmentioning
confidence: 88%
“…So far, there are only a few examples of gene-environmental interactions implicated to play a role in the development of type 1 diabetes. The findings in two case-control studies suggested that there might be an interaction between increased genetic disease susceptibility, based on HLA class II alleles, and an early introduction of supplementary milk feeding during infancy on the risk of type 1 diabetes (88,89). A Finnish study indicated that the increased relative risk associated with childhood milk consumption may be higher among siblings of affected children carrying HLA class II genotypes conferring strong or moderate disease susceptibility than among those with low or decreased risk genotypes (63).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest decreased rates of sudden infant death syndrome in the first year of life [49][50][51][52][53][54][55] and reduction in incidence of insulin-dependent (type 1) and non-insulin-dependent (type 2) diabetes melli- [56][57][58][59] lymphoma, leukemia, and Hodgkin disease, 60-62 overweight and obesity, 19,63-70 hypercholesterolemia, 71 and asthma [36][37][38][39] in older children and adults who were breastfed, compared with individuals who were not breastfed. Additional research in this area is warranted.…”
Section: Other Health Outcomesmentioning
confidence: 99%